Mechanical vibration and shock analysis. Volume 1, - Lalanne, Christian (ISTE : Wiley, 2014)
Everything engineers need to know about mechanical vibration and shock ... in one authoritative reference work! This fully updated and revised 3rd edition addresses the entire field of mechanical vibration and shock as one of the most important types of load and stress applied to structures, machines and components in the real world. Examples include everything from the regular and predictable loads applied to turbines, motors or helicopters by the spinning of their constituent parts to the ability of buildings to withstand damage from wind loads or explosions, and the n.
Keywords: Condensed matter.; Damping (Mechanics); Shock (Mechanics); Vibration.; elektronické knihy; electronic books